2012
DOI: 10.3109/08916934.2012.702814
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-17A and -17F gene single-nucleotide polymorphisms with autoimmune thyroid diseases

Abstract: Th17 lymphocyte and its relative cytokines have been shown to play an important role in autoimmune thyroid diseases (AITD). The aim of this study was to investigate the association between IL-17A and IL-17F gene polymorphisms and two main types of AITD, Graves' disease (GD) and Hashimoto's thyroiditis (HT). Whole blood specimens and clinical data were collected from 508 AITD patients (326 with GD and 182 with HT) and 224 age- and gender-matched healthy controls, respectively. IL-17A (rs2275913, rs8193037, rs38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
1
39
0
1
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs) of inflammatory cytokines may change the transcription rate and consequently the production of cytokines (Dominici et al 2002, Wen et al 2006, Prasad et al 2010, and thus may modify individual susceptibility to AITDs. Various cytokines and respective genetic polymorphisms have been reported to be associated with AITD, but the results are inconsistent (Chen et al 2005, Shiau et al 2006, Anvari et al 2010, Liu et al 2010, Yan et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) of inflammatory cytokines may change the transcription rate and consequently the production of cytokines (Dominici et al 2002, Wen et al 2006, Prasad et al 2010, and thus may modify individual susceptibility to AITDs. Various cytokines and respective genetic polymorphisms have been reported to be associated with AITD, but the results are inconsistent (Chen et al 2005, Shiau et al 2006, Anvari et al 2010, Liu et al 2010, Yan et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Tregs in peripheral tissues play an important role in the maintenance of peripheral immune tolerance and the prevention of autoimmune diseases. Th17 cells have been observed to play a role in numerous autoimmune diseases, and there is more evidence suggesting that they are related to GD (Ganesh et al 2011, Horie et al 2011, Yan et al 2012. This nonhuman primate model which more closely approximates human GD is the prerequisite for GD vaccine in rhesus monkeys and would potentially shorten the distance toward the prevention and treatment of this disease in human beings in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the IL-23A gene, some IL-23-related genes also have been investigated to be associated with the risk of GD. Yan et al concluded that in the Chinese population, IL-17F/rs763780 polymorphisms may affect the susceptibility to AITD, and IL-17A/rs3819025 SNP was likely a protective factor to GD [22]. Huber et al found that in the North American Caucasian, variants of the IL-23 receptor gene were strongly associated with GO [21].…”
Section: Discussionmentioning
confidence: 95%
“…[4]. Recently, several IL-23-related genes such as the IL-23 receptor gene and the IL-17A gene have been shown to be associated with susceptibility to GD [21,22]. These results imply that the IL-23 gene may be a candidate gene predisposing to GD.…”
Section: Introductionmentioning
confidence: 82%